Effects of a national work hours restriction in a high hours country - Jieun Lee (IZA Journal of Labor Policy, 2022)
This paper examines the effect of a new maximum work hour restriction introduced in South Korea in 2018 that limited maximum working hours from 68 h/week to 52 h/week. I use difference-in-differences analysis with continuous treatment measuring the prevalence of those working longer than 52 h/week prior to the policy change across industry-occupation-education groups. I find that the policy reduces work hours while increasing monthly earnings and hourly wages for male full-time workers. However, I find that the policy does not significantly affect total work hours, total employment, and total worker pay at the industry-occupation-education group level.
Keywords: J81; J22; 330; Work hour restriction; Labor regulation; Difference-in-differences with continuous treatment; South Korea